Comparative genomics reveal pathogenicity‐related loci in Pseudomonas syringae pv. actinidiae biovar 3. (26th April 2019) - Zhao, Zhibo; Chen, Jiliang; Gao, Xiaoning; Zhang, Di; Zhang, Jinlong; Wen, Jing; Qin, Huqiang; Guo, Ming; Huang, Lili
Summary: Bacterial canker of kiwifruit, is a severe global disease caused by Pseudomonas syringae pv. actinidiae (Psa). Here, we found that Psa biovar 3 (Psa3) was the only biovar consisting of three widely distributed clades in the largest Chinese kiwifruit cultivated area. Comparative genomics between the three clades revealed 13 polymorphic genes, each of which had multiple intra‐clade variations. For instance, we confirmed that the polymorphic copA gene, which encodes a periplasmic protein CopA that is translocated by the Twin‐arginine targeting (Tat) system, was involved in copper tolerance. We also found extensive variation in pathogenicity amongst strains within each genetically monomorphic clade. Accordingly, the pathogenic determinants of Psa3 were identified via a genomic comparison of phenotypically different strains within each clade. A case study of the high‐ and low‐virulence strains in the clade 2 of Psa3 revealed that an hfq variant involved in in vitro growth and virulence, while a conserved locus 930 bp upstream of the hrpR gene in the Type III secretion system (T3SS) cluster was required for full pathogenicity on kiwifruit and elicitation of the hypersensitivity response on non‐host Nicotiana benthamiana . The '‐930' locus is involved in transcriptional regulation of hrpR/S and modulates T3SS function via the hierarchical 'HrpR/S‐HrpL‐T3SS/effector' regulatory cascade in Psa. Our results provide insights into the molecular basis underlying the genetic diversification and evolution of pathogenicity in Psa3 since kiwifruit canker emerged in China in the 1980s.